2011
DOI: 10.3390/medicina47090073
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Bimanual Task Performance

Abstract: Background and Objective. Many studies have suggested that each hand has a different special talent; however, there is a lack of data in the area of goal-directed bimanual hand coordination and its dependence on gender. The aim of this paper was to investigate gender-dependent bimanual speed-accuracy task performance. Material and Methods. Twelve healthy young males and twelve healthy young females (all righthanded) performed protractile movements with both arms simultaneously by pushing joysticks toward two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The authors suggested that gender difference in reaction time performance may reflect differences in processing strategy. Other researcher achieved confusing results that there was no significant difference in RT between people of both gender during a unimanual speed-accuracy task, however during a bimanual task, the reaction time of both hands was significantly longer in women than men (Mickevičienė et al, 2011 ). We didn't find significant differences in the slopes of the linear models describing reaction time and error rate (see Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that gender difference in reaction time performance may reflect differences in processing strategy. Other researcher achieved confusing results that there was no significant difference in RT between people of both gender during a unimanual speed-accuracy task, however during a bimanual task, the reaction time of both hands was significantly longer in women than men (Mickevičienė et al, 2011 ). We didn't find significant differences in the slopes of the linear models describing reaction time and error rate (see Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results stay in line with the data from Larson et al that females and subjects high on neuroticism made significantly fewer errors in a choice reaction-time task (Larson and Saccuzzo, 1986 ). In an experiment with the bimanual task the accuracy of the left hand was significantly greater in men than women (Mickevičienė et al, 2011 ). Thus, we can report the presence of some gender-dependent features of task performance.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from an impact of age and cognitive functioning on interhemispheric neural networks, previous studies have also reported sex differences with a greater relative callosal area of women than men in the splenium of the CC (Davatzikos and Resnick, 1998), but with age having a stronger impact on CC diffusivity in women than men (Sullivan et al, 2010). Only few studies have investigated sex effects on bimanual coordination, those who did reported slight female disadvantages (Mickeviciene et al, 2011;Shetty et al, 2014). To the best of our knowledge, no study has investigated the interaction between age and sex on bimanual coordination including bimanual force control.…”
Section: Introductionmentioning
confidence: 99%
“…23 The present study also demonstrated an absence of sexual dimorphism influence on MRT before or after four weeks of resistance training, despite gender differences to withstand exercise load, fatigue sensation, 24 or hand muscle structure. 25 Possibly, because the motor task applied in our study evaluated only the dominant hand to perform it, according to Mickeviciene et al 11 Thus, it is also reasonable to hypothesize that there is sexual dimorphism influence on MRT in performing activities with both hands. 11 Despite this hypothesis, there is no evidence about the reaction time of both hand activities and gender differences.…”
Section: Discussionmentioning
confidence: 92%
“…4 Besides, even among several factors that may interfere in RT, sexual dimorphism 11 and physical exercise 4 are discussed in the literature. 4,11 In this sense, strength and muscle fiber differences between men and women can influence on Manual Reaction Time (MRT). 12 Another sex difference that also can change MRT is the hormone and menstrual cycle.…”
mentioning
confidence: 99%